2012
DOI: 10.5812/ircmj.2153
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of the Efficacy of KID21 Point (Youmen) Acupressure on Nausea and Vomiting of Pregnancy

Abstract: BackgroundNausea and vomiting in pregnancy is a common complaint of nearly 50-80% of pregnant women. The problem begins around the 4th weeks of pregnancy and often stays up to the 12th weeks and may continue to the 16th week in a few patients.ObjectivesThe aim of our study is to determine the effect of acupressure (on KID21 point) on nausea and vomiting of pregnancy.Materials and MethodsThis single blind clinical trial study was performed on 80 women with nausea and vomiting in the first trimester of pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 12 publications
(14 reference statements)
0
40
0
Order By: Relevance
“…In the context of non-pharmacological therapy use, studies on acupressure as a strategy to reduce discomforts of pregnancy have been developed essentially for nausea and vomiting (7)(8) . However, there is evidence that acupressure can be performed on individuals affected by more than one clinical symptom (5) .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of non-pharmacological therapy use, studies on acupressure as a strategy to reduce discomforts of pregnancy have been developed essentially for nausea and vomiting (7)(8) . However, there is evidence that acupressure can be performed on individuals affected by more than one clinical symptom (5) .…”
Section: Introductionmentioning
confidence: 99%
“…A research conducted in 2012 confirmed the positive impact of applying pressure on this point in reducing pregnancy nausea and vomiting. (37) …”
Section: Discussionmentioning
confidence: 99%
“…13,41,57,60,[62][63][64]66,67,69,70,76,[80][81][82][83][85][86][87][88][89]91,93,94,[98][99][100][101][102][103][104][106][107][108]110,[112][113][114][115] Methods employed included random number tables, computer-generated sequence generation 61,63,64,[81][82][83]88,93,94,98,99,106,108,…”
Section: Random Sequence Generationmentioning
confidence: 99%
“…57,60,61,63,64,66,67,73,76,78,[80][81][82][83][84][85]88,89,93,98,99,102,103,[105][106][107][108]112,118 Thirty studies did not provide sufficient information to allow a judgement of low or high risk and were therefore classed as unclear. 13,[41][42][43]58,59,62,65,[68][69][70][71]74,75,77,79,90,91,[94][95][96][97]100,…”
Section: Allocation Concealmentmentioning
confidence: 99%
See 1 more Smart Citation